Vegetative propagation of Jatropha species by stem cuttings - Gaikwad, Rajesh Shrirangrao (Current Botany, 2011)
Investgation carried out on rooting of stem cuttings of Jatropha curcas and J. gossypifolia. Cuttings were treated with different combinations of auxins.along with distilled water (control). Stem cuttings of J. curcas, IAA+IBA at 300 ppm was proved significantly effective for percent rooting and more number of leaves.